2022
DOI: 10.7554/elife.74056
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-138 controls hippocampal interneuron function and short-term memory in mice

Abstract: The proper development and function of neuronal circuits relies on a tightly regulated balance between excitatory and inhibitory (E/I) synaptic transmission, and disrupting this balance can cause neurodevelopmental disorders, e.g. schizophrenia. microRNA-dependent gene regulation in pyramidal neurons is important for excitatory synaptic function and cognition, but its role in inhibitory interneurons is poorly understood. Here, we identify miR138-5p as a regulator of short-term memory and inhibitory synaptic tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…[ 59 ]), where it is thought to promote the early stages of oligodendrocyte differentiation while preventing their final maturation, thereby facilitating the correct selection of axons and appropriate myelination [ 59 ]. No staining was detectable among GFAP-stained astrocytes in agreement with observations in the brain by Daswani and cols [ 57 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…[ 59 ]), where it is thought to promote the early stages of oligodendrocyte differentiation while preventing their final maturation, thereby facilitating the correct selection of axons and appropriate myelination [ 59 ]. No staining was detectable among GFAP-stained astrocytes in agreement with observations in the brain by Daswani and cols [ 57 ].…”
Section: Discussionsupporting
confidence: 91%
“…A similar distribution is observed in the spinal cord of mice ( Mus musculus C57BL/6J strain) according to ongoing studies from the lab (see Uceta [ 56 ]). In fact, regionalization of neuronal expression of miR-138-5p is also observed in the brain [ 46 , 55 , 57 ] and seems common among microRNAs (see, for example, miR-34 expression in spine neurons in Chang and cols. [ 58 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampal slices from male animals derived from the genetic deletion (WT vs cKO), AAV deletion and Myl9/Mustn1 overexpression cohorts (300 μm thick) were prepared at 4 °C, as previously described [46]…”
Section: Electrophysiologymentioning
confidence: 99%
“…In cortical structures most of the work has focused on PNs. However, recent research has demonstrated crucial roles for miRNAs in INs, from early development (survival, specification, and lamination of medial ganglionic eminence-derived INs) to cognitive functions and memory formation (Daswani et al, 2022; Qiu et al, 2020; Tuncdemir et al, 2015).…”
Section: Introductionmentioning
confidence: 99%